Age Matters: Community Assembly in the Pig Fecal Microbiome in the First Month of Life - Jurburg, Stephanie D.; Bossers, Alex (Frontiers in Microbiology, 2021)
Despite the wealth of research into strategies for microbiome modulation, studies of microbiome management in pig hosts have found mixed results. A refined understanding of the patterns of microbiome assembly during the host’s early life, when management strategies are most commonly applied, is necessary for the development of successful management practices. Here, we study the development of the pig gut microbial community in a monitoring experiment, sampling the microbiome of pigs in a commercial farm intensively during the first month of life. We found that the community’s taxonomic richness increased linearly with host age. Furthermore, rapid changes across communities occurred in stages, and non-linear patterns in relative abundance were commonly observed among dominant taxa across host age, consistent with primary succession. Our results highlight the importance of understanding the patterns of microbiome assembly during host development, and identify successional stages as windows of opportunity for future research.